Facebook-Based E-Portfolio Assessment in An EFL Classroom: Design, Enactment, and Evaluation - Syairofi, Ahmad; Waluyo, Budi (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Although many studies have attempted to explore the viability of Facebook for educational purposes, little attention has been paid to the employment of Facebook as a platform for e-portfolio assessment in reading classes for vocational high school students. To fill this void, this case study aimed to design, enact, and evaluate a Facebook-based e-portfolio assessment. This study adopted Lam’s (2013) logistics of the portfolio process. The data was obtained from the researcher’s and participants’ documents, observations, and interviews. Then, thematic analysis was employed to analyze the data qualitatively. The findings revealed that the instructional design for this e-portfolio assessment made the participants enjoy the learning process and promote literacy activities. The design scaffolded and engaged participants with technological activities, while the enactment process promoted active learning. The evaluation promoted self-directed learning as the participants could revise their works and choose which works to be assessed. The implications of the study and future directions were also discussed.